Monitoring of Measurement Reliability in Power Systems on the basis of Statistical Decision Theory - V. A. Anishchenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers the monitoring problem of measurement reliability in power systems applying a semantic method of limiting values. Critical analysis of the existing approach to optimization of the decision making boundaries which is based on the Bayes criterion is given in the paper. It is proposed to use a minimax criterion which makes it possible to solve the optimization problem under the conditions of initial uncertainty in the notions of gross error and unreliability of measurements. Values of eiToneous decisions of the 1st and 2nd kinds are specified by taking into account random measurement errors and substitution of the unreliable measurement results.